2014
DOI: 10.21101/cejph.a3905
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Determinants of Metabolic Syndrome among Roma and Non-Roma Subjects in the Eastern Part of Slovakia

Abstract: Our study confirmed that the prevalence of metabolic syndrome is strongly associated with hypertriglyceridemic waist, besides other risk factors, a marker of the atherogenic metabolic triad among younger Roma population, which may be the reason for the increased cardiovascular (CV) morbidity and mortality in elderly Roma compared with non-Roma. In light of these results, better prevention of CV events for Roma minority settlements in Slovakia should be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
1
7
0
5
Order By: Relevance
“…This finding indicates the presence of an increased low-grade systemic inflammation in Roma population compared to non-Roma counterparts most likely due to an increased cardiometabolic risk. These observations correlate well with previous findings [ 2 , 39 ] and further support the idea that the Roma are at increased risk for cardiovascular and metabolic diseases [ 4 , 5 ]. Other risk factors previously reported in Roma (smoking, obesity, lack of physical activity) could contribute to the low-grade systemic inflammation in the Roma population.…”
Section: Discussionsupporting
confidence: 92%
“…This finding indicates the presence of an increased low-grade systemic inflammation in Roma population compared to non-Roma counterparts most likely due to an increased cardiometabolic risk. These observations correlate well with previous findings [ 2 , 39 ] and further support the idea that the Roma are at increased risk for cardiovascular and metabolic diseases [ 4 , 5 ]. Other risk factors previously reported in Roma (smoking, obesity, lack of physical activity) could contribute to the low-grade systemic inflammation in the Roma population.…”
Section: Discussionsupporting
confidence: 92%
“…Metabolic syndrome was diagnosed in 29.2% of Roma population, but only in 20.7% of the majority population (17). Dyslipidemia with decreased levels of HDL cholesterol was also more prevalent in the Roma population compared to the majority (18).…”
Section: Editorial Low Socioeconomic Status and Unhealthy Lifestyle Lmentioning
confidence: 95%
“…Earlier, the obesity and MetS were reported to depend on ethnicity and gender which prevalent more in the Russians than in the Chuvashes population in Chuvash Republic (Markova et al, 2014). Nevertheless, the MetS components values were reported to be different between Roma and non-Roma subjects in the eastern part of Slovakia (Fedacko et al, 2014). Earlier studies conducted on the northern part of Iran obesity was found less in Turkman group than in Fars-native group (Veghari & Mansurian, 2007;Veghari et al, 2010b).…”
Section: Methodsmentioning
confidence: 91%
“…The different cut-off point of WC for MetS was seen in different ethnic groups in African especially in men (Hoebel , 2013). In addition, the prevalence of MetS and some other related factors were reported to vary in some studies among different ethnic groups (Veghari , 2010b;Markova , 2014;Fedacko 2014;Veghari & Mansurian, 2007;Ford , 2002;Guo , 2014). The cut-off point of age for MetS had also not been reported in previous studies, however outstanding result of our study was the determine of age cut-off for MetS based on ethnic groups.…”
Section: Methodsmentioning
confidence: 99%